Faktor-faktor yang Memengaruhi Partisipasi Masyarakat Petani dalam Kegiatan Rehabilitasi Hutan dan Lahan (RHL) di Kabupaten Gorontalo (Studi Kasus di Desa Bontula kawasan Hutan Nantu dan Taman Hutan Raya BJ. Habibie) - Irnawati Dania; Mahludin H. Baruwadi; Siti Rahmatia Machieu (Universitas Galuh, 2026)
The Forest and Land Rehabilitation (RHL) Program requires active community involvement, particularly from farmers who interact directly with forest areas. This study aims to analyze the influence of farmer commitment, farmer competence, and bureaucratic support on community participation in RHL activities in Bontula Village. The research employed a quantitative approach using survey techniques, involving 48 farmer respondents. Data were analyzed using multiple linear regression to determine the effect of each independent variable on participation levels. The results show that the level of farmer participation falls within the medium to high category, with a percentage score of 64.29%. Statistical findings indicate that farmer commitment and bureaucratic support have a significant effect on participation, with significance values of 0.008 and 0.013, respectively. Conversely, farmer competence does not show a significant influence, with a significance value of 0.220. These results confirm that the success of the RHL program is more influenced by motivational factors and institutional support than by farmers’ technical abilities. This study recommends strengthening farmer commitment and improving the quality of bureaucratic support as key strategies to enhance community participation in forest rehabilitation activities in Bontula Village.